GSM based cathodic protection SCADA system [GSM tabanli katodi̇k koruma SCADA si̇stemi̇] - (:unkn) unknown (My University, 2008)
Monitoring cathodic protections of steel and pre-stressed concrete cylinder pipes used in water supplies is realized by a GSM and microprocessor based SCADA system. Instead of using manual methods, automatically measuring the cathodic protection parameters such as system potential, pipe ground potential and anode current over GSM network are successfully achieved. All the relevant data are stored in a database and reported when needed. The whole water supply system is monitored in real-time via GSM. By applying the cathodic protection criteria for steel and pre-stressed concrete cylinder pipes, each measurement point is remotely determined through a control algorithm to check whether the cathodic protection is at satisfactory level.
Keywords: Anode current; Cathodic protection; GSM/SMS; Pipe ground potential; SCADA; System potential